2020
DOI: 10.1158/1940-6207.capr-20-0036
|View full text |Cite
|
Sign up to set email alerts
|

Blood Supply of Early Lung Adenocarcinomas in Mice and the Tumor-supplying Vessel Relationship: A Micro-CT Angiography Study

Abstract: This study aimed to investigate the blood supply of early lung adenocarcinomas in mice and the relationship between tumors and their supplying vessels by using micro-CT. An early lung adenocarcinoma model was established in 10 female mice with subcutaneous injections of a 1-methyl-3-nitro-1-nitrosoguanidine solution. Micro-CT pulmonary and bronchial arteriography were performed to demonstrate the blood supply of early lung adenocarcinomas, especially the tumor–vessel relationships, and the findings were correl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Furthermore, blood flow contributions to metastatic lesions occurring in a given organ were estimated using micro-CT in a hepatic colorectal metastasis mouse model [ 116 ]. It has been shown that micro-CT angiography can clearly demonstrate the morphologic changes of vessels and their relationships with tumors [ 117 ]. Compared with other techniques for tumor vessel morphologic evaluation and measurement of vessel content, micro-CT has several additional features.…”
Section: Untrodden Path: Vasculature Access In Sarcomasmentioning
confidence: 99%
“…Furthermore, blood flow contributions to metastatic lesions occurring in a given organ were estimated using micro-CT in a hepatic colorectal metastasis mouse model [ 116 ]. It has been shown that micro-CT angiography can clearly demonstrate the morphologic changes of vessels and their relationships with tumors [ 117 ]. Compared with other techniques for tumor vessel morphologic evaluation and measurement of vessel content, micro-CT has several additional features.…”
Section: Untrodden Path: Vasculature Access In Sarcomasmentioning
confidence: 99%
“…Each set contained two simulated tumors. Tomography 2021, 7,5 to that of the original micro-CT acquisition of the healthy mouse. Similarly, a second volume which contained the parenchyma behind the synthesized tumors was created and forward projected (Figure 2, part 2).…”
Section: Data Augmentation With Simulated Image Generationmentioning
confidence: 99%
“…A critical metric of therapeutic response in patients is metastasis-free survival determined through serial imaging of the lungs, the most common site for metastasis for this type of soft tissue sarcoma. Micro-CT has been successfully used to detect lung tumors and evaluate lung tumor burden in many mouse models [6,7]. To mimic the clinical arm of the study and patient standard of care, we perform periodic micro-CT scans of free-breathing mice to detect lung metastasis after treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The pulmonary arterial trees are responsible for oxygenating the blood supply and dispelling byproducts of systemic cellular respiration, while the bronchial (or systemic) arterial trees provide oxygenated blood specifically to lung tissue for their own cellular respiration. This dual blood supply feature of the lungs is also shared with lung tumors (Milne, 1967), and resolving the extent to which the different vascular networks are involved in tumor initiation, growth, histology, and metastasization is an active field of research (Nguyen-Kim et al, 2015;Eldridge et al, 2016;Deng et al, 2020).…”
Section: Pulmonary Vs Bronchial (Systemic) Arterial Networkmentioning
confidence: 99%